Monitoring of seed viability and longevity after storage in Purwodadi Botanic Garden Seed Bank, Pasuruan, Indonesia - FITRI BLESSFATH ENFAITH; GEBBY AGNESSYA ESA OKTAVIA; DEWI AYU LESTARI; ESTI ENDAH ARIYANTI (Asian Journal of Agriculture, 2026)
Abstract. Enfaith FB, Oktavia GAE, Lestari DA, Ariyanti EE. 2026. Monitoring of seed viability and longevity after storage in Purwodadi Botanic Garden Seed Bank, Pasuruan, Indonesia. Asian J Agric 10: g100107. https://doi.org/10.13057/asianjagric/g100107. Seed longevity is determinant of efficiency of storage practice. Seed viability after storage needs to be monitored to determine seed longevity. Seed viability of selected seed in the Purwodadi Botanic Garden (PBG) Seed Bank, Pasuruan, Indonesia, was monitored to predict the seed longevity after storage. The material used was selected seed species that have been stored in low temperature storage (-20°C) in hermetic storage at the Purwodadi Botanic Garden Seed Bank since 2016 (7 years storage), i.e., Aleurites moluccana, Cassia grandis, C. javanica, Colona scabra, Hura crepitans, Ixora miquelii, Pterospermum diversifolium, Sterculia foetida and Swinglea glutinosa. Seeds from each species were sown in sand as the planting medium, were then observed to perceive the germination percentage, the seed viability percentage, and the seed longevity. The results showed that all selected seeds experienced a decrease in germination percentage and even lost their ability to germinate. Seed longevity varies from very short with a decreasing rate of >30% (H. crepitans, I. miquelii, P. diversifolium, S. glutinosa and S. foetida), short with a decreasing rate of 15-30% (C. javanica and C. scabra), medium with a decreasing rate ranging from 4-15% (C. grandis), to long-lived seeds with a decreasing rate of <5% (A. moluccana). SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis was conducted to determine conservation strategies for seeds stored in the PBG Seed Bank. The result was that the appropriate conservation strategy for the PBG Seed Bank was assertive or proactive.